Identification and control of fungi associated to stored ’cagaita’ (Eugenia dysenterica DC.) seeds - Gomide, Cynthia Correia Costa; da Fonseca, Carlos Eduardo Lazarini; Nasser, Luis Carlos Bhering; Charchar, Maria José D'Ávila; Neto, Austeclino L. de Farias (Pesquisa Agropecuaria Brasileira, 1994)
In order to identify fungi associated to seeds of ’cagaita’ and to evaluate the effect of 8 fungicide treatments on fungal control and germination, two experiments were carried out at EMBRAPA-CPAC research station. In the first experiment, seeds were treated and stored in a humid cold chamber for one day before being sowed in flats filled with sand. The same was done for the second one, but seeds were stored for 50 days before sowing. Evaluation was done for percentage of infected seeds, percentage of emergence, and speed of emergence. Fungi isolated from seeds were Alternaria, Aspergillus, Cladosporium, Curvularia, Helminthosporium, Mucor, Nigrospora, Penicillium, and Rhizopus. Seeds soaked in a 5% aqueous solution of Benomyl for ten minutes promoted the best results for fungal control and emergence speed and rate. This treatment also accelerated the germination of seeds stored for one day period. Treatments either with sodium hypochlorite or with Carboxin + Thiram were phytotoxic to seedlings of cagaita.